THE EFFECT OF STORY MAPPING STRATEGY ON STUDENTS’ READING COMPREHENSION: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL SYNTHESIS - Fakhrul Rijal; Zaki Al Fuad; Ali Salim Ali Razaq (Sensei International Journal of Education and Linguistic, 2025)
Many students can read the text but they do not understand what the story is about. Story mapping is one of the strategies that can help the students to understand the story because they must find the character, setting, problem, and solution. This article discusses the effect of the story mapping strategy on students' reading comprehension. The method used is literature review. The result shows that story mapping can improve the reading comprehension of the students, especially for the narrative text. But the teacher must guide the students at first because they are not used to making the map. Therefore story mapping is good to be applied in the reading class.